PENGGUNAAN APLIKASI Si YOKCA UNTUK MEMPERMUDAH MENGAKSES BERBAGAI LAYANAN DI BALAI LAYANAN PERPUSTAKAAN DPAD DIY YOGYAKARTA - Alfiyani, Siti; Wahidi, Wahidi (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2024)
This research is entitled The Use of the Si Yokca Application to Make it Easier to Access Various Services at the DPAD DIY Yogyakarta Library Service Center. The research method uses descriptive qualitative research where the data sources obtained are the results of observations of the use of the si Yokca application. The data collection technique in this study uses a direct observation approach, documentation, and in-depth interviews conducted with 1 library manager as the informant, Si Yokca stands for let's read! An application that is an invitation to the community to always read. Each library member can find the latest and featured books. Information on book availability can also be checked and then ordered and borrowed with just one click. Books that have been borrowed can be monitored through the history page, along with information on when they will be returned. The app is equipped with a digital member card that makes it easy to access library services without the need to print a member card.